CircEPSTI1 Promotes the Proliferation of HER2-Positive Breast Cancer Cells via circEPSTI1/miR-145/ERBB3 Axis. (26th August 2022) - Zhang, Yue; Tan, Duxun; Xie, Yi; Wu, Linyu; Wu, Song; Tang, Yuhui; Luo, Yongzhou; Xiao, Xiangsheng; Li, Xing
Abstract : Breast cancer is the most common type of cancer worldwide. There are great challenges in the prevention and treatment of breast cancer. In this study, we explored the molecular and biological mechanisms of circular RNA circEPSTI1 (has_circ_0000479) in the regulation of HER2-positive breast cancer cells. The expression of CircEPSTI1, microRNA miR-145, and ERBB3 in HER2-positive breast cancer cells was evaluated by qRT-PCR and western blot assays. Cell proliferation was assessed by CCK-8. Wound-healing and transwell migration assays were performed to evaluate cell migration. A transwell invasion assay was performed to detect cell invasion. The interaction of miR-145, circEPSTI1, and ERBB3 was confirmed bydual-luciferase reporter and RIP assays. CircEPSTI1 was upregulated in the HER2-positive breast cancer tissues and cells. Knockdown of circEPSTI1 inhibited SKBR3 and BT474 cell proliferation, migration, and invasion. Mechanistically, circEPSTI1 directly targeted miR-145, and miR-145 was a downstream mediator of circEPSTI1 in modulating the proliferation, migration, and invasion of SKBR3 and BT474 cells. ERBB3 was identified as a direct and functional target of miR-145 in HER2-positive breast cancer cells. Our findings demonstrate that circEPSTI1, an overexpressed circRNA in HER2-positive breast cancer, promotes the proliferation, migration, and invasion of SKBR3 and BT474 cells through the miR-145/ERBB3 axis.